Pendekatan Kepemimpinan dan Kepribadian dalam Personal Branding Prabowo Subianto di TikTok @partaigerindra - Krisnadiyanti, Safira Puspa; Achmad, Zainal Abidin (Journal of Management, Education and Communication, 2024)
This study aims to comprehend the personal branding of Prabowo Subianto as a prospective presidential candidate for the 2024 election through the TikTok account @partaigerindra. The research employs a descriptive qualitative methodology. The findings indicate that the personal branding strategy utilized by Prabowo Subianto on the official TikTok account @partaigerindra, based on the eight personal branding concepts by Montoya and Vandehey, predominantly aligns with the concepts of leadership and personality. In terms of leadership, the TikTok account @partaigerindra effectively showcases Prabowo Subianto's ability to manage his authority to address public concerns. Prabowo demonstrates pro-people leadership in his roles as Minister of Defense and presidential candidate. Regarding personality, the TikTok account @partaigerindra portrays Prabowo Subianto as a leader capable of engaging with both the public and journalists through its posts, supported by approachable and friendly captions.